Application of Improved (G'/G)–Expansion Method to Traveling Wave Solutions of Two Nonlinear Evolution Equations (Advances in Applied Mathematics and Mechanics, 2012)
In this work, the improved (G'/G)-expansionmethod is proposed for constructing more general exactsolutions of nonlinear evolution equation with the aid of symboliccomputation. In order to illustrate the validity of the method wechoose the RLW equation and SRLW equation. As a result, many new andmore general exact solutions have been obtained for the equations. Wewill compare our solutions with those gained by the other authors.